La actividad lúdica en el desarrollo motriz en el Centro de Educación Inicial Lucerito en el subnivel 2 grupo de 3 a 5 años durante el año lectivo 2020-2021. - Chifla Chuncho, Verónica Maricela (2021)
The present research aims to establish a set of recreational activities for the development of gross motor skills for boys and girls of initial level 2 group of 3 to 5 years of the Lucerito Initial Education Center, through which the development of the gross motor skills of boys and girls. To determine the level of knowledge about playful activities of teachers and children, the qualitative-quantitative methodology was used with techniques and instruments such as: the survey, interview and the observation sheet. Analyzing the instruments used in children, the need to improve motor skills was detected through a proposal focused on recreational activities, in the Lucerito Initial Education Center in its application to children, common movements typical of their age were carried out, who The problem in coordination, balance and laterality, which includes developing this type of research, which will observe, in the simple way, the lack of the three fundamental aspects mentioned above. The results show that 90% of the children achieved a significant improvement in motor development, compared to those in 10% who are in a moderate range. The results show that the proposed "Guide of ludic activities" contributed significantly to the development of motor skills, that is, its application and continuity is feasible. Concluding with the research, motor development links emotions to the practice of playful activities, due to constant learning which encourages the development of social, communicative and motivational skills when interacting with other subjects, forming part of the educational process.